Application of Fe-doped TiO2 specimens for the solar photocatalytic degradation of humic acid - Birben, Nazmiye Cemre; Uyguner-Demirel, Ceyda Senem; Sen Kavurmaci, Sibel; Gurkan, Yelda Yalcin; Turkten, Nazli; Cinar, Zekiye; Bekbolet, Miray (ELSEVIER SCIENCE BV, 2017)
This study aimed to assess solar photocatalytic activity of Fe-doped TiO2 specimens for the degradation of natural organic matter (NOM) represented by a model humic acid (HA). Fe-doped TiO2 specimens (P-25 and UV-100) were prepared by a wet impregnation method. Humic acid (molecular size < 100 kDa) was characterized by UV-vis and fluorescence spectroscopic parameters and dissolved organic carbon (DOC) content both prior to and following solar photocatalysis. Molecular size fractionation data revealed a shift to lower molecular size fractions i.e.: 30 kDa, 10 kDa and 3 kDa being more pronounced in case of Fe-doped UV-100 in comparison to Fe-doped P-25. Excitation-emission matrix (EEM) fluorescence features of indicated humic molecular size fractions did not illustrate any significant difference related to the formation of new fluorophoric regions but displayed the shift from humic-like fluorophores to fulvic-like fluorophores even in 3 kDa fraction indicating that humic acid followed a photocatalyst type independent pathway via solar photocatalysis. Slower DOC removal rates were attained for Fe-doped TiO2 specimens with respect to bare specimens indicating the importance of substrate properties rather than the inefficiency of visible light activation by metal doping of photocatalyst. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: EEM; Fe-doped TiO2; Humic acid; Molecular size distribution; Solar photocatalytic degradation; VISIBLE-LIGHT; TITANIUM-DIOXIDE; ORGANIC-MATTER; SPECTROSCOPY; AROMATICITY; MECHANISMS; OXIDATION; DYNAMICS; SIZE; Chemistry; Engineering